Tutoring in (Online) Higher Education: Experimental Evidence - David Hardt; Markus Nagler; Johannes Rincke (Center for Economic Studies and ifo Institute (CESifo), 2022)
Demand for personalized online tutoring in higher education is growing but there is little research on its effectiveness. We conducted an RCT offering remote peer tutoring in micro- and macroeconomics at a German university teaching online due to the Covid-pandemic. Treated students met in small groups, in alternating weeks with and without a more senior student tutor. The treatment improved study behavior and increased contact to other students. Tutored students achieved around 30% more credits and a one grade level better GPA across treated subjects. Our findings suggest that the program reduced outcome inequality. We find no impacts on mental health.
Keywords: I20; I23; I24; I10; 330; tutoring; higher education; online teaching; Covid; mental health